2018
DOI: 10.1016/j.cedpsych.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Relations among math self efficacy, interest, intentions, and achievement: A social cognitive perspective

Abstract: Drawing on social cognitive perspectives, the present study examined an integrative model of the interplay among math self-efficacy, interests, aspirations, and achievement among early and middle adolescents. Based on short-term longitudinal data from approximately 400 students, analyses using fully latent structural equation analyses, establishing requisite levels of longitudinal invariance, revealed that (a) math self-efficacy positively predicted math achievement using both class grades and standardized tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 86 publications
(168 reference statements)
9
66
0
7
Order By: Relevance
“…This study makes a contribution by confirming that the agency of interest in achievement can hardly be recorded, at least as it is generally measured, when controlling for neighbouring perceptual constructs such as self-concept. This research seems to align with other similar results that were obtained in recent math education studies (Denissen et al, 2007;Ganley & Lubienski, 2016;Grigg et al, 2018;Nuutila et al, 2018;Skaalvik & Skaalvik, 2004;Xu, 2018), suggesting a certain transdisciplinary conformity of the constructs considered.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This study makes a contribution by confirming that the agency of interest in achievement can hardly be recorded, at least as it is generally measured, when controlling for neighbouring perceptual constructs such as self-concept. This research seems to align with other similar results that were obtained in recent math education studies (Denissen et al, 2007;Ganley & Lubienski, 2016;Grigg et al, 2018;Nuutila et al, 2018;Skaalvik & Skaalvik, 2004;Xu, 2018), suggesting a certain transdisciplinary conformity of the constructs considered.…”
Section: Resultssupporting
confidence: 91%
“…Based on their own review of the literature, Grigg et al argued that previous available evidence is in line with this hypothesis, and were also able to confirm it through a longitudinal panel design in Australia (Grigg et al, 2018). Other longitudinal designs that controlled for (sometimes many) other possible covariables were also able to confirm rather strong bidirectional, reciprocal interaction between achievement and self-concept in Korea (Lee, Lee, & Bong, 2014), China (Xu, 2018), and Finland (Nuutila et al, 2018).…”
Section: What About the Relationship Between Self-concept And Achievementioning
confidence: 89%
“…Participation in science and math activities predicted American students' expectancy and value beliefs, which in turn predicted the number of science and math courses taken in high school (Simpkins et al, 2006). A separate study also demonstrated the bidirectional link between math interest and future intentions to pursue math and science-related courses and careers (Grigg et al, 2018). Research from four OECD countries using TIMSS data revealed links between high academic achievement in a science domain with enhanced motivation in the same domain, which in turn predicted domain-specific aspirations (Guo et al, 2017).…”
Section: Future Plans In Sciencementioning
confidence: 85%
“…Las diferencias entre el grupo medio y el grupo pequeño también alcanzaron la significatividad estadística, siendo mediano (d = 0.77) el tamaño de estas diferencias. Olivier et al, 2019), sobre los procesos de autorregulación del aprendizaje (Vancouver, 2018;Zimmerman et al, 2005) y, finalmente, sobre el rendimiento (Grigg et al, 2018;Hoigaard et al, 2015;Schöber et al, 2018). La relación entre autoeficacia y percepción del dominio del ambiente evidenciada en el presente estudio pone de manifiesto la importancia de desarrollar intervenciones tendentes a potenciar esta última en el contexto universitario.…”
Section: Discussionunclassified